A Citation Analysis and Bibliometric Graph of Human Evacuation Research - Yixuan Huang; Rui Li; Yunhe Tong; Wei Xie (Fire)
Effective evacuation is vital for minimizing casualties during disasters. This study employed the Web of Science (WOS) database to perform a bibliometric analysis of the evacuation literature. VOSViewer (v1.6.20) and CiteSpace (v6.3.R1) software were used to visualize publication trends, international collaboration networks, keyword co-occurrence, clustering, and keyword bursts. The findings indicate that three research focuses are foundational to advancing the field of evacuation research, with shifts in these areas reflecting the dynamic nature of the field’s transition. Four key research themes outline the core content of the field’s investigation. Furthermore, this study identifies three key research phases in evacuation: the theoretical model development and foundational research phase, the behavioral dynamics and advanced simulation phase, and the data-driven intelligence and practical application phase. Future directions of evacuation research are discussed. This study provides a comprehensive analytical framework that deepens the understanding of the evacuation field.